1999
DOI: 10.1097/00005650-199901000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Access to Coronary Artery Bypass Surgery by Race/Ethnicity and Gender Among Patients Who Are Appropriate for Surgery

Abstract: Even after controlling for appropriateness and necessity for coronary artery bypass graft surgery in a prospective study, African-American patients had significant access problems in obtaining coronary artery bypass graft surgery. These problems appeared not to be related to patient refusals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(104 citation statements)
references
References 29 publications
1
100
1
2
Order By: Relevance
“…Many studies have identified differences in the utilization of medical interventions on the basis of sex and race [1,3,4,14,16,19,21,35,38,39,45]. The spectrum of medical interventions, from preventive to diagnostic, is affected by sex and race, even after adjusting for diagnosis and severity of illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have identified differences in the utilization of medical interventions on the basis of sex and race [1,3,4,14,16,19,21,35,38,39,45]. The spectrum of medical interventions, from preventive to diagnostic, is affected by sex and race, even after adjusting for diagnosis and severity of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly less utilization of some surgical interventions is well documented among women, including orthopaedic procedures [19]. Some interrelated elements may affect services utilization after a patient has entered the medical system, including patient preferences for and acceptance of procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Our study included a number of rheumatologists, and it is likely that physicians' communications to patients varied, perhaps differing by ethnic group. We suspect, however, that this potential bias may be more marked for lifestyle behavior changes (e.g., sun or pregnancy avoidance) as well as processes such as referral patterns (22), which vary among patients and which are more complex and dependent on physician-patient communication. In contrast, the routine recommendations to take medications and to keep scheduled appointments are usually communicated in systematic ways to all patients (e.g., via prescriptions or written appointments or monitored by additional clinic staff).…”
Section: Discussionmentioning
confidence: 99%
“…We focused these vignettes on cardiac care, given the well-supported evidence that blacks and women, despite clinically equivalent circumstances, are less likely to receive cardiac care procedures. 1,[19][20][21][22][23][24][25][26][27][28][29][30][31] Two clinically equivalent options for recommendations, one involving a procedure and the other a non-procedural option, were developed for each vignette. The vignettes were created under the premise that in situations where clinical equivalency does not allow a clear choice, social psychology concepts would suggest that students would then be forced to base their decisions on secondary, non-clinical factors, such as patient demographics.…”
Section: Methodsmentioning
confidence: 99%